Street Children in Butwal Municipality: A Case Study - Bhusal, Shivalal (Tribhuvan University Journal, 2016)
There is ever existence of homeless, poor, orphaned, abandoned and working children in the world. In the traditional societies, those children were absorbed by the extended family or other are said to be' street children'. Street children are the products of so called modern, social and economic systems. Unless the systems are revised properly, the problem of street children would remain as it is. Nevertheless, they have a right to safety, shelter, and the other basic necessities of life. Therefore, state and development parlers need to show obligations to design and implement relevant and functional forms of interventions. This article looks at the situations of street children in Butwal municipality and presents a short glimpse of the problem.